Penyerapan Logam Fe Dengan Menggunakan Karbon Aktif Dari AmpasTebu Yang Diaktifasi Dengan KOH - Roni Roni; Drastinawati Drastinawati; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bagasse is one of the agricultural or industrial waste that has potential for an adsorbent. Adsorbents produced from bagasse is processed by the pyrolys process. This study aimed to examine the effect of activated carbon absorption of ferrous metals with concentrations variations of KOH and adsorptiontime, and to study the characteristics of the activated carbon produced, among others, ash content and moisture content. This research was conducted in three phases, namely the preparation of raw materials, the manufacture of activated carbon, and the absorption of Fe in FeSO4 solution. Variations in the concentration of KOH used in this study were 0%, 5%, 10%, and 15%. As for the time variation adsorbs used were 30, 60, and 90 minutes. Percent absorption is the best obtained when the concentration of 15% KOH and adsorbs time of 90 minutes is equal to47%.Keywords: adsorbent, adsorption time, bagasse, KOH concentration.